Pengaruh Teknik Pernapasan Buteyko Terhadap Penurunan Kekambuhan Asma Pada Pasien Asma Bronkhial - Orita Satria; Fitri Apriani; Siti Damayanti; Dinda Muharamah (BALE LITERASI, 2025)
Background: Atshma is a respiratory problem characterized by breathing difficulties due to airway inflammation or constriction. One method that could be used to improve breathing patterns is through the application of the buteyko breathing technique. It reduces hyperventilation by controlling breath reduction, potentially decreasing the frequency of bronchial asthma patients. Methods: This study employed an experimental design with a one-group pretest-posttest approach, involving 37 participants. Results: Based on statistical analysis, the buteyko breathing technique demonstrated a significant effect, with a pre-test p value of 0,000 and a post-test p-value of 0,000. Conslusion: The quantitative findings of this study confirm that the buteyko breathing technique effectively reduces asthma recurrence in bronchial asthma patients at Johan Pahlawan Health Center condicts health promotion and provides education on non-pharmacological approaches to managing asthma recurrence to enhance community awareness and understanding of bronchial asthma.